Relato de experiência: as aulas práticas no aprendizado dos alunos da disciplina de reprodução e inseminação artificial - Liberalino Lima, Gabriela; Ferreira Barbosa Fernandes, Maria Aparecida (Faculdade de Filosofia e Ciências, 2020)
In the teaching-learning process, practical activities gain prominence, as they allow the observation and application of technical knowledge in a way that this experience would not be possible with theory alone. Specific contents cover concepts and techniques that are difficult to understand only in theory, even when using other resources such as videos and case studies, in addition, certain skills can only be developed or improved through practical classes. This is noticeable within the discipline of Reproduction and Artificial Insemination of the Bachelor of Zootechnics course. The aim of this study is to report a practical class experience in the discipline of Reproduction and Artificial Insemination of the Bachelor of Zootechnics course and the perception of the importance of these practices by students. The method adopted in the present project was the description of the realization of a practical class and presentation of the students' reports through the practical class reports elaborated by them. The results show that the practical class provides a favorable environment for the participation and interaction among the students, so that at some point in the class there was a 100% participation of the class. This approach also allows the development of technical skills required for the formation of the future professional bachelor in Zootechnics. Thus, a practical class in the Reproduction Biotechnology laboratory can be configured as a successful methodological tool in the discipline of Reproduction and Artificial Insemination.